Oral Cancer Awareness among Dental Patients - Bajracharya, Barsha; Dahal, Anita; Deo, Rajeeb Kumar (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: The incidence of oral cancer in South Asian countries, including Nepal is increasing despite the fact that all of its risk factors are modifiable. This can be attributed to lack of awareness regarding oral cancer and its risk factors among general public. This study was conducted among subjects attending Dental OPD of a tertiary hospital to assess the knowledge and attitude regarding oral cancer and also practices of risk factors associated with it. Methods: This is a questionnaire based cross-sectional study conducted from July 2020 to October 2020. Subjects attending Dental OPD of a tertiary hospital in Kathmandu were asked to fill a structured close-ended Questionnaire. Section one of the questionnaire focused on the demographic data of the subjects, second part elicited information pertaining to knowledge of oral cancer, third part focused on attitude and fourth part on practices of participants towards risk factors of oral cancer. Result: Out of 300 subjects, 65% were males. Most were in the age group 41 - 50 years and 75.6% were literate. Majority mentioned smokeless tobacco as the risk factor, followed by smoking and alcohol. Regarding signs and symptoms, most of the participants mentioned non-healing ulcer, followed by lump and pain. Most of the participants responded tongue as the most common site of oral cancer. Majority answered that oral cancer can be prevented by not chewing tobacco. Among the total, 55.3% said oral cancer is non-contagious. Only 25% had undergone oral examination in the last one year. 31.7% had habit of tobacco and / or alcohol. Conclusions: The awareness level and knowledge about risk factors and early signs of oral cancer in this cross-section of dental patients were satisfactory. Key words: awareness; oral cancer; risk factors; tobacco